Tropical Futurism Aesthetics: The Impact of Latin American Women's Urban Art on Social Change - Bladimir Enrique Cedeño-Vega (eTropic: electronic journal of studies in the tropics)
This article examines the impact of women’s urban art of Latin America, emphasizing how artists have utilized public spaces to construct visual discourses that challenge sociocultural norms and promote gender justice. By integrating elements of popular culture, advertising visual language, and plural feminist thought, these artists transform their work into aesthetic tools of cultural resistance. The analysis explores how feminist visual narratives are enriched through decolonial, tropicalizing, rhizomatic, and tropical futurism aesthetic approaches, enabling diverse interpretations that challenge traditional visual paradigms. In countries such as Brazil, Mexico, Argentina, Bolivia, Colombia, Chile, Ecuador, Panama, and Puerto Rico, as well as their diasporas, artistic interventions have sparked discussions on women’s rights and directly confronted patriarchal structures. These practices democratize access to art, strengthen cultural identity, and embody a futuristic re-imagination of tropical spaces as inclusive, resilient, and transformative. Women’s urban art reconfigures cultural urban landscapes, fostering social activism, strengthening the social fabric, and reshaping public perceptions of gender and equality. Ultimately, this movement serves not only as a form of artistic expression but also as a catalyst for sociocultural change, a defense of women’s rights, and a vision of a more equitable and dynamic tropical future.